Photodynamic and photothermal bacteria targeting nanosystems for synergistically combating bacteria and biofilms - Xiao Wang; Wenxuan Shi; Yu Jin; Zhuoyuan Li; Tanjun Deng; Tingshu Su; Ao Zheng; Lingyan Cao (Journal of Nanobiotechnology)
Abstract The escalating hazards posed by bacterial infections underscore the imperative for pioneering advancements in next-generation antibacterial modalities and treatments. Present therapeutic methodologies are frequently impeded by the constraints of insufficient biofilm infiltration and the absence of precision in pathogen-specific targeting. In this current study, we have used chlorin e6 (Ce6), zeolitic imidazolate framework-8 (ZIF-8), polydopamine (PDA), and UBI peptide to formulate an innovative nanosystem meticulously engineered to confront bacterial infections and effectually dismantle biofilm architectures through the concerted mechanism of photodynamic therapy (PDT)/photothermal therapy (PTT) therapies, including in-depth research, especially for oral bacteria and oral biofilm. Ce6@ZIF-8-PDA/UBI nanosystem, with effective adhesion and bacteria-targeting, affords a nuanced bacterial targeting strategy and augments penetration depth into oral biofilm matrices. The Ce6@ZIF-8-PDA/UBI nanosystem potentiated bacterial binding and aggregation. Upon exposure to red-light (RL) irradiation, Ce6@ZIF-8-PDA/UBI showed excellent antibacterial effect on S. aureus, E. coli, F. nucleatum, and P. gingivalis and exceptional light-driven antibiofilm activity to P. gingivalis biofilm, which was a result of the efficient bacterial localization mediated by PDA/UBI, as well as the PDT/PTT facilitated by Ce6/PDA interactions. Collectively, these versatile nanoplatforms augur a promising and strategic avenue for controlling infection and biofilm, thereby holding significant potential for future integration into clinical paradigms. The original application of the developed nanosystem in oral biofilms also provides a new strategy for effective oral infection treatment.